The role of quantum effects on structural and electronic fluctuations in neat and charged water. - Giberti, F; Hassanali, A; Ceriotti, M; Parrinello, M (2014)
In this work, we revisit the role of nuclear quantum effects on the structural and electronic properties of the excess proton in bulk liquid water using advanced molecular dynamics techniques. The hydronium ion is known to be a weak acceptor of a hydrogen bond which gives it some hydrophobic character. Quantum effects reduce the degree of this hydrophobicity which facilitates the fluctuations of the protons along the wires compared to the classical proton. Although the Eigen and Zundel species still appear to be dominant motifs, quantum fluctuations result in rather drastic events where both transient autoionization and delocalization over extended proton wires can simultaneously occur. These wild fluctuations also result in a significant change of the electronic properties of the system such as the broadening of the electronic density of states. An analysis of the Wannier functions indicate that quantum fluctuations of neat water molecules result in transient charging with subtle similarities and differences to that of the excess proton.